2022
DOI: 10.3390/fermentation8080363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cereals and Legumes Processing on In Situ Rumen Protein Degradability: A Review

Abstract: The determination of the ruminal degradability rate of feeds, mainly starch and crude protein, is one of the most common methods to evaluate the nutritional value of ruminant feed. The protein requirements for ruminants are met from microbial protein and undegraded dietary protein digested in the small intestine. In order to reach maximum productivity, high-quality proteins are needed, and the requirement for undegraded dietary protein increases with the performance of the animal. This protein can be supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
2
7
0
1
Order By: Relevance
“…As the nutritional value of a feed does not depend exclusively on its nutrient content but also on the extent of ruminal degradation, it was observed that the sum of the digestible fractions (B1, B2, and B3) was greater in the coconut cakes (88%) and palm kernel cake (81.11) than in corn (64.45%) and soy (76.64), the conventional ingredients. The values found are compatible with other works, where the protein degraded in the rumen is 75–80% for soybeans and from 52 to 65% for corn [ 22 , 35 , 36 , 37 ]. However, there is also a comment on digestible protein’s amino acid composition and the investigation’s importance [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…As the nutritional value of a feed does not depend exclusively on its nutrient content but also on the extent of ruminal degradation, it was observed that the sum of the digestible fractions (B1, B2, and B3) was greater in the coconut cakes (88%) and palm kernel cake (81.11) than in corn (64.45%) and soy (76.64), the conventional ingredients. The values found are compatible with other works, where the protein degraded in the rumen is 75–80% for soybeans and from 52 to 65% for corn [ 22 , 35 , 36 , 37 ]. However, there is also a comment on digestible protein’s amino acid composition and the investigation’s importance [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…La tasa de degradabilidad ruminal de alimentos, principalmente almidón y proteína, es uno de los métodos más comunes para evaluar el valor nutricional de los alimentos para rumiantes. Los rumiantes satisfacen sus requerimientos de proteínas con la proteína microbiana y la proteína no degradada en rumen (RUP) (Iommelli et al, 2022). La proteína degradada en rumen (RDP) se mide mediante la degradabilidad in situ con la técnica de la bolsa de nylon (Mehrez & Ørskov, 1977); (Ørskov & McDonald, 1979).…”
Section: Degradabilidad De La Proteína En Rumenunclassified
“…Starch changes structurally and gelatinizes when heated in the presence of water. Its crystal structure also disintegrates, and its solubility and rheological properties are altered [39]. When combined with modification methods for starches, the difference in particle size, fiber content, pelletizing, extruding, pressure toasting, and other feed production techniques may significantly alter how starch in compound feeds breaks down in the rumen [40].…”
Section: Kinetics Of Gasmentioning
confidence: 99%
“…LA treatment has the ability to slow the enzymatic action of amylases in grains [42]. Moreover, Deckardt et al [39] demonstrated that, compared to dry-rolled barley, the gas volume was reduced early on, and the gas production constant rate increased after 24 h of steeping barley in water containing 7.5 g of LA.…”
Section: Kinetics Of Gasmentioning
confidence: 99%
See 1 more Smart Citation